2019
DOI: 10.1097/iae.0000000000002281
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Therapy for Refractory Birdshot Chorioretinopathy

Abstract: The results suggest that adalimumab is effective at improving visual acuity and at tapering concomitant immunomodulatory therapy, in patients with refractory birdshot chorioretinopathy. However, complete remission is rarely achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…The amount of evidence available steadily increased and, nowadays, indicates that aggressive and sustained immunosuppressive therapy is needed for the long-term treatment of BRC [ 27 , 28 ]. There is no specific agent that can be recommended but most conventional immunosuppressive [ 29 , 30 , 31 ] as well as biological agents [ 32 , 33 , 34 ] have been found to be efficient. The approach by trial and error has become possible as indocyanine green angiography was found sensitive for the monitoring of activity [ 35 ] giving rapid information on the efficacy or lack of efficacy of an agent in any given case, allowing fine-tuning of treatment [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of evidence available steadily increased and, nowadays, indicates that aggressive and sustained immunosuppressive therapy is needed for the long-term treatment of BRC [ 27 , 28 ]. There is no specific agent that can be recommended but most conventional immunosuppressive [ 29 , 30 , 31 ] as well as biological agents [ 32 , 33 , 34 ] have been found to be efficient. The approach by trial and error has become possible as indocyanine green angiography was found sensitive for the monitoring of activity [ 35 ] giving rapid information on the efficacy or lack of efficacy of an agent in any given case, allowing fine-tuning of treatment [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, one approach may function for one patient and not for another. Biologic agents represent additional therapeutic possibilities and have been shown to be useful [ 32 , 33 , 34 ]. However, for these therapies also, only trial and error will guide the clinician.…”
Section: Managementmentioning
confidence: 99%
“…Adalimumab obtained FDA approval for intermediate and posterior non-infectious uveitis based on the results of the VISUAL trial, a multicenter randomized phase 3 study in which 30 out of the 229 patients included had a birdshot chorioretinopathy [ 80 ]. Adalimumab has also been shown to be effective in improving the visual acuity in a report of 19 patients with BSCR refractory to immunosuppressive drugs, but complete remission was rarely achieved [ 81 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Here, it is good to consider that the cause of HLA-A29-dependent BU is most likely heterogenous and in some patients may be mediated by genetic susceptibility imprinted in ERAP genes, while in others ERAPs may be dysregulated by alternative mechanisms. For example, ERAP1 is tightly regulated by TNF-alpha, a pro-inflammatory cytokine that is increased in concentration in eye fluids of BU patients and blocking TNF-alpha by anti-TNF therapy alleviates severe symptoms of BU (67)(68)(69)(70). Polymorphisms linked to ERAP1 and ERAP2 genes are also associated with other HLA class I associated conditions that manifest with non-infectious uveitis, including HLA-B27-associated anterior uveitis and ankylosing spondylitis, or HLA-B51-associated Behcet's disease (71)(72)(73).…”
Section: The Erap1-erap2 Haplotype Links Bu To the Western-european Ancestrymentioning
confidence: 99%